The Influence of Organizational Routines and Agility on Branch Performance: The Mediating Role of Managerial Discretion - Darlene Monica Damopolii; Lily Sudhartio (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: In today's rapidly evolving banking landscape, Indonesian financial institutions face increasing pressure to remain competitive, responsive, and customer-centric. While digital transformation continues to shape the industry, branch offices remain integral to operational and strategic outcomes, especially in delivering services and maintaining long-term customer trust. Within this setting, branch heads serve as middle managers who are expected to make swift and context-sensitive decisions. However, their decision-making authority is often constrained by rigid organizational routines, creating a paradox where agility is required, yet formal structures dominate. This dynamic presents a unique challenge: how can branch-level leaders balance routine procedures with the agility needed to meet market demands and drive performance?.Purpose: This study investigates how branch performance is shaped by the interaction between organizational routines and agility, and the mediating role of managerial discretion.Design/methodology/approach: This study was conducted at Bank XYZ, a state-owned bank in Indonesia. The population consisted of branch heads from Class B.I and B.II branches. Using the Slovin formula (confidence level: 93%, margin of error: 7%), a minimum sample of 136 was targeted. Out of 165 distributed questionnaires, 142 valid responses were obtained. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Findings/Result: The results indicate that the variables pertaining to organizational routines and organizational agility serve to reinforce the significant role of managerial discretion in the performance of Bank XYZ branches, which can be evaluated across five performance dimensions: financial, quality, innovation, environment, and social. Conclusion: The findings demonstrate that organizational routines remain a key aspect of banking branch operations. However, in contexts that demand flexibility and speed in implementing changes and seizing opportunities, the role of managerial discretion becomes particularly crucial in enabling the application of agility to achieve performance.Originality/value (State of the art): This study contributes valuable insights into the complex relationship between organizational routines, agility, and managerial discretion, particularly in the context of banking branch operations. It emphasizes how managerial discretion is essential in balancing routine operations and the need for flexibility in dynamic environments, offering a framework to improve branch performance in challenging situations. Keywords: branch performance, managerial discretion, organizational agility, organizational routines, achieve performance